Aminomethylphosphonic Acid (AMPA), a Glyphosate Metabolite, Decreases Plasma Cholinesterase Activity in Rats - Jesús Chávez-Reyes; Fernando Saráchaga-Terrazas; Oliver Alejandro Colis-Arenas; Carlos H. López-Lariz; Carlos M. Villalón; Bruno A. Marichal-Cancino (Journal of Xenobiotics, 2024)
Glyphosate, a widely used herbicide, is linked to a plethora of deleterious effects in both clinical and preclinical studies. Nevertheless, the effects of its main metabolite, aminomethylphosphonic acid (AMPA), whose half-life in soil is even longer than that of glyphosate, have been little explored. On this basis, as a first approach, in this work, we report that intraperitoneal (i.p.) administration of AMPA or glyphosate (at 10, 56, and 100 mg/kg) decreased, to a similar extent, plasma cholinesterase (ChE) activity in acutely exposed rats. Moreover, we designed an experimental protocol to analyze and compare the effects of AMPA and glyphosate on human plasma ChE activity; this protocol consisted of adding these compounds to human plasma to subsequently test the effects of this plasma on the contraction to acetylcholine (ACh) in the frog rectus abdominis muscle (an indirect estimate of ChE activity). Accordingly, this muscular contraction to ACh was evaluated before and after pre-incubation of ACh with (i) plasma alone, (ii) plasma with AMPA, and (iii) plasma with glyphosate. Our results indicate that AMPA, like glyphosate, decreased ChE activity in the plasma of rats (when given i.p.) and humans (when added in vitro), suggesting that both xenobiotics may exert similar toxicological effects.